A Comparison between the Asset-oriented and Needs-based Community Development Approaches in Terms of Systems Changes. Issue 1 (1st January 2018) - Nel, Hanna
Abstract : In this study, a comparison was undertaken between the asset-based community development (ABCD) approach versus the more traditional needs-based approaches to community development. The study was done by means of an exploratory, descriptive and contextual strategy inquiry conducted within a qualitative paradigm. Although both approaches led to changes on personal, organisation and community levels, changes differed in various ways in these three systems. The ABCD approach succeeded in enabling community members to engage and participate meaningfully with each other, and undergo consciousness changes from a poverty-influenced mindset to citizens who created and drove their projects in the community. The community members led their own development by co-investing their own assets, and enhanced these with assets from the outside. In comparison, communities not sensitised to ABCD were usually driven by the organisations, based on the needs and problems of communities. Securing funds for development initiatives and the rendering of services seemed to be a major focus. Communities who followed the problem-based approach were better off in the short-term, although projects showed less signs of sustainability.